Embedded Librarianship in Scholarly Communication: Perceived Roles of Academic Librarians in Malaysian Research Intensive Universities - M. H., Azura; A., Abrizah (2015)
When scholarly communication is placed at the forefront of Malaysian research universities, the need for a research arm to support and facilitate usage, publishing and dissemination of research output becomes crucial has and this has changed the academic libraries’ services landscape. This paper reports the results of a study that aims to understand the practices of embedded librarianship in Malaysian research universities. The paper explores the embedded librarian’s in the pre-publication and post-publication roles of the scholarly communication process. Data were collected through personal semi structured interviews with twelve respondents from five academic libraries. Findings show that the academic libraries are expected to take a greater responsibility for the usage and dissemination of publication output of research intensive universities, as the participants in general perceived that the survival of the professionalism requires the embedded librarianship practices.